The Influence of K-12 Language Teachers' Demographic Profiles on Authentic Assessment Practice - Hailay Tesfay Gebremariam; Abate Demissie Gedamu (Indonesian Journal of Applied Linguistics, 2023)
While much literature has been used to investigate authentic assessment practice in the field of education, particularly in the context of language classrooms, a study investigating the demographic profiles of teachers and their relation to authentic assessment practice in language classrooms is crucial and needs further exploration. To this end, the current study investigated the K-12 language teachers' demographic profiles in relation to their authentic assessment practice, in terms of gender, teaching experience, and educational status. The study included 282 K-12 teachers enrolled in a summer program. The study design was a descriptive survey, and data were obtained via a questionnaire. Descriptive and inferential statistics were used to analyze the gathered data. Results showed that language teachers had significant differences (p .05) in classroom questioning and discussion (hereafter referred to as CQD), as well as substantial differences (p .05) in peer and self-assessment (hereafter referred to as PSA) and feedback process (hereafter referred to as FB). Additionally, significant differences (p .05) were observed in the effect of gender, teacher experience, and educational status on all three subsections. The findings show that although language teachers had authentic assessment practice, there were no consistent results regarding the influence of their background information. These findings contribute to our understanding of how demographic profiles of language teachers affect authentic assessment practice in K-12 education. Based on the results of the study, recommendations have been made for further consideration.